2012
DOI: 10.1186/1710-1492-8-14
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, immunological and genetic features in eleven Algerian patients with major histocompatibility complex class II expression deficiency

Abstract: Presenting processed antigens to CD4+ lymphocytes during the immune response involves major histocompatibility complex class II molecules. MHC class II genes transcription is regulated by four transcription factors: CIITA, RFXANK, RFX5 and RFXAP. Defects in these factors result in major histocompatibility complex class II expression deficiency, a primary combined immunodeficiency frequent in North Africa. Autosomal recessive mutations in the RFXANK gene have been reported as being the principal defect found in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 29 publications
2
16
0
Order By: Relevance
“…dysmorphic features, transaminitis, oral HPV and candidiasis, thrush, purulent otitis, neurological manifestations, genitourinary infections, eczema and Molluscum contagiosum. 8,9 The exclusive manifestation of these symptoms in patients with group B MHC II deficiency should be further studied.…”
Section: Clinical Findingsmentioning
confidence: 99%
“…dysmorphic features, transaminitis, oral HPV and candidiasis, thrush, purulent otitis, neurological manifestations, genitourinary infections, eczema and Molluscum contagiosum. 8,9 The exclusive manifestation of these symptoms in patients with group B MHC II deficiency should be further studied.…”
Section: Clinical Findingsmentioning
confidence: 99%
“…In fact, several studies have reported a founder effect for the RFXANK gene mutation 752delG26 in these patients. [46,48,49,55,59] In 2011, Ouederni et al [55] dated the founder event responsible for this mutation in this population to ~2 250 years ago. A study by Ben-Mustapha et al [44] in 2014 reported a common founder…”
Section: Novel Mutations In the African Populationmentioning
confidence: 96%
“…Many studies in the northern region of Africa describe an autosomal recessive transmission mode for PIDs and some have reported novel autosomal recessive gene mutations. [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] Due to this fact, the northern region of Africa seems to be a distinctive epidemiological area for the study of genetic diseases, such as PIDs, which has drawn the attention of many researchers in the past decade. Table 5 illustrates some of the studies describing molecular characterisation, novel genetic mutations and founder effects of PIDs undertaken mainly in Africa.…”
Section: Novel Mutations In the African Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…2,8,9 It is known to occur in families with a high degree of consanguinity, as would be expected of a rare autosomal recessive disorder. This is highlighted in patient 2 of our series, where the parents were first cousins.…”
mentioning
confidence: 99%